2022
DOI: 10.3390/su14052855
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Meat and Bone Meal (MBM) on Phosphorus (P) Content and Uptake by Crops, and Soil Available P Balance in a Six-Year Field Experiment

Abstract: The aim of a six-year field experiment conducted in north-eastern (NE) Poland was to determine the effect of meat and bone meal (MBM) on phosphorus (P) content and uptake by different crops, soil available P balance, and soil pH. Five treatments were established: (1) zero-fert; (2) inorganic NPK; (3) 1.0 t ha−1 MBM; (4) 1.5 t ha−1 MBM; and (5) 2.0 t ha−1 MBM. Constant nitrogen (N) and potassium (K) rates and increasing P rates (0.0; 45; 68 and 90 kg ha−1) were applied. The lowest dose of MBM, which supplied 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The combination of 25% nano bone ash and 75% SP-36 resulted in improved leaf area and fresh shoot weight compared to using 100% SP-36 without foliar rice husk ash. These results align with the research conducted by Załuszniewska & Nogalska (2022), where the application of meat and bone provided better results for winter oilseed rape and winter wheat compared to commercial NPK fertilizers. Another study conducted by Maulidayanti et al (2023) on edamame soybeans demonstrated that the application of nano bone ash at a concentration of 0.15% and a frequency of 3 times was able to substitute up to 50% of the requirement for SP36 fertilizer.…”
Section: Plant Growthsupporting
confidence: 90%
“…The combination of 25% nano bone ash and 75% SP-36 resulted in improved leaf area and fresh shoot weight compared to using 100% SP-36 without foliar rice husk ash. These results align with the research conducted by Załuszniewska & Nogalska (2022), where the application of meat and bone provided better results for winter oilseed rape and winter wheat compared to commercial NPK fertilizers. Another study conducted by Maulidayanti et al (2023) on edamame soybeans demonstrated that the application of nano bone ash at a concentration of 0.15% and a frequency of 3 times was able to substitute up to 50% of the requirement for SP36 fertilizer.…”
Section: Plant Growthsupporting
confidence: 90%
“…In the study of Zaluszniewska and Nogalska [77], C18:1 oleic acid, C18:2 linoleic acid, and C18:3 α-linolenic acid accounted for nearly 90% of the fatty acids in rapeseed, and their proportions did not change under the influence of mineral fertilisation and meat and bone meal. In their study, the ratio of linoleic acid (C18:2) to α-linolenic acid (C18:3) was 1.81:1, which they consider to be the optimal ratio.…”
Section: Discussionmentioning
confidence: 97%
“…Bone meal, a popular organic fertilizer derived from finely ground animal bones, is rich in P (15-27%) and Ca (22-33%) [80]. Bone meal also contains a small amount of N (1-4%) and trace minerals, including collagens.…”
Section: Bone Mealmentioning
confidence: 99%